GEOACOUSTIC LOCATION OF EARTHQUAKE PREPARATION AREAS - Gordienko V.A.; Gordienko T.V.; Kuptsov A.V.; Larionov I.A.; Marapulets Yu.V.; Shevtsov B.M.; Rutenko A.N. (My University, 2006)
High-frequency geoacoustic emission during the preparation of strong earthquakes in Kamchatka is characterized by an intensification of radiation for a few hours before the seismic event and coincidence of the signal bearing with the direction to the stress source, which is sometimes located at a distance of several hundred kilometers from the observation point. Taking into account strong attenuation of high-frequency acoustic oscillations in the hypocenter and the impossibility of their registration at great distances, it is possible to explain the nature of the forerunners by the propagation of strains from the earthquake source as short-period shocks before the beginning of the earthquake.